REORGANIZACIJA POSLOVANJA KAO NAČIN REŠAVANJA INSOLVENTNOSTI - Milošević, Isidora (International Journal of Economic Practice and Policy, 2022)
A long-term insolvency period usually precedes commencement of bankruptcy proceeding, by which time a debtor has already used up most of their assets. Such company has already lost its place on the market, been abandoned by the company's best workers, and has not maintained or renewed the equipment. These are all indicators of the company's need of fresh capital required for effective reorganization. Reorganization provides the debtor with an opportunity to ''revive'', provided that reorganization has to be cost-efficient for the creditors, who will make decision on the course of action, toward insolvency or bankruptcy. Bankruptcy proceeding should be completed with as low costs as possible, as soon as possible and as effective outcomes as possible in order to ensure a regular economic course. The legal system can generate fundamental risk factors for bankruptcy, whereby not only regulations but rather implementation of the law are involved. Duration and costs of a bankruptcy proceeding, and sometimes incompetent bankruptcy administrators and other people involved in the proceeding can add to the debtor's bad position and further deepen insolvency of the business entities involved. Bankruptcy reorganization also affects existing agreements between the debtor and creditors but measures affecting rights of the owner of all the debtor’s assets may also apply, which essentially includes their private property. The aim is to sustain functioning of the business entity as a unit including all its business relationships and employees because this can assign the business entity the value higher than the value of individual sales of the debtor’s assets.
Keywords: reorganization plan; bankruptcy reorganization; legal system; adopted plan; satisfying creditors